Redescription, new distribution record, DNA sequence and length-weight relationship of the Eel-loach Pangio pangia (Cypriniformes: Cobitidae) in the River Ganges Basin, India - Sarkar, U. K. (2013)
The Eel-loach Pangio pangia has never been reported from East India in the River Ganges. In August, 2011, we collected a total of 39 individuals of this species during fish diversity explorations in River Ganges at Narora. This is the first record for Uttar Pradesh (North India). We present additional diagnostic features and description for this species previously known only from very old descriptions generally based on preserved specimens. Additionally, a molecular signature of the internal transcribed spacer 2 (ITS2) region between 5,8S and 28S ribosomal RNA genes was sequenced and submitted to NCBI (Accession No. JQ619873). The length-weight relationship showed allometric growth as b value of overall length-weight relation was 2,71 at p<0,00 which, ranged from 2,65 to 2,76. The substantial threats and issues regarding unawareness of this understudied fish species are highlighted to help sustaining fish biodiversity in India. KEY WORDSNew distribution, Pangio pangia, length weight relationship, River Ganges, India.